Dynamic history of the Central Plain and Haidai region inferred from Late Neolithic to Iron Age ancient human genomes - Hui Fang; Fawei Liang; Hao Ma; Rui Wang; Haifeng He; Limin Qiu; Le Tao; Kongyang Zhu; Weihua Wu; Long Ma; Huazhen Zhang; Shuqing Chen; et al. (Cell Reports)
Summary: The peopling history of the Yellow River basin (YR) remains largely unexplored due to the limited number of ancient genomes. Our study sheds light on the dynamic demographic history of the YR by co-analyzing previously published genomes and 31 newly generated Late Neolithic to Iron Age genomes from Shandong in the lower YR and the Central Plain in the middle YR. Our analysis reveals the population structure in Shandong and the Central Plain in the Late Neolithic Longshan cultural period. We provide a genetic parallel to the observation of a significant increase in rice farming in the middle and lower YR in the Longshan period. However, the rice-farmer-related gene flow in the Longshan period did not arrive in groups from the Yuzhuang sites in the Central Plain or previously published groups in Shandong. The Bronze Age Erlitou culture genomes validate the genetic stability in the Central Plain and the relative genetic homogeneity between the Central Plain and Shandong.